HLA alleles associated with COVID-19 susceptibility and severity in different populations: a systematic review - Meryem Fakhkhari; Hayat Caidi; Khalid Sadki (Egyptian Journal of Medical Human Genetics, 2023)
Abstract Background COVID-19 is a respiratory disease caused by a novel coronavirus called as Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Detected for the first time in December 2019 in Wuhan and it has quickly spread all over the world in a couple of months and becoming a world pandemic. Symptoms of the disease and clinical outcomes are very different in infected people. These differences highlight the paramount need to study and understand the human genetic variation that occurring viral infections. Human leukocyte antigen (HLA) is an important component of the viral antigen presentation pathway, and it plays an essential role in conferring differential viral susceptibility and severity of diseases. HLA alleles have been involved in the immune response to viral diseases such as SARS-CoV-2. Main body of the abstract Herein, we sought to evaluate this hypothesis by summarizing the association between HLA class I and class II alleles with COVID-19 susceptibility and/or severity reported in previous studies among different populations (Chinese, Italian, Iranian, Japanese, Spanish, etc.). The findings of all selected articles showed that several alleles have been found associated with COVID-19 susceptibility and severity. Even results across articles have been inconsistent and, in some cases, conflicting, highlighting that the association between the HLA system and the COVID‐19 outcome might be ethnic‐dependent, there were some alleles in common between some populations such as HLA-DRB1*15 and HLA-A*30:02. Conclusion These contradictory findings warrant further large, and reproducible studies to decipher any possible genetic predisposition underlying susceptibility to SARS-COV-2 and disease progression and host immune response.